2015
DOI: 10.1155/2015/967165
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nonpoint Source Pollution and Water Environmental Quality Variation Trends in the Nansi Lake Basin from 2002 to 2012

Abstract: Based on the data analysis of economic development and the water environmental quality from 2002 to 2012 in the Nansi Lake Basin in China, the correlation between economic development and the water environmental quality was researched. Analysis shows that the GDP of the Nansi Lake Basin had an average annual growth of 7.3% in 2012, and the COD andCODMnhad the average annual decrease of 7.69% and 6.79%, respectively, compared to 2002. Basin water environmental quality overall improved, reaching Class III of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Wu et al (2015) have described nonpoint source pollution as originating from diffuse sources such as urban runoff and soil erosion, which affect receiving waters such as lakes, rivers or reservoirs caused by leaching and erosion of rainfall runoff, agricultural as well as anthropogenic activities (Ridolfi, 2016). Wang et al (2015) found that agricultural nonpoint source pollution contributed between 68% to 83% of the total pollution, including nitrogen, phosphorus, nutrients, and organic and inorganic pollutants exposed to surface runoff. According to Zhang et al (2013), another factor affecting nonpoint sources is improper land use structure and management, leading to soil erosion and pollutant-induced water eutrophication.…”
Section: Point Sources Of Pollution and Nonpoint Sources Of Pollutionmentioning
confidence: 99%
“…Wu et al (2015) have described nonpoint source pollution as originating from diffuse sources such as urban runoff and soil erosion, which affect receiving waters such as lakes, rivers or reservoirs caused by leaching and erosion of rainfall runoff, agricultural as well as anthropogenic activities (Ridolfi, 2016). Wang et al (2015) found that agricultural nonpoint source pollution contributed between 68% to 83% of the total pollution, including nitrogen, phosphorus, nutrients, and organic and inorganic pollutants exposed to surface runoff. According to Zhang et al (2013), another factor affecting nonpoint sources is improper land use structure and management, leading to soil erosion and pollutant-induced water eutrophication.…”
Section: Point Sources Of Pollution and Nonpoint Sources Of Pollutionmentioning
confidence: 99%
“…The existing academic research on the impact of Chinese livestock production on water pollution mainly concentrated in the fields of agronomy and chemistry. These studies revealed various water pollutants and heavy metals produced by livestock production from the view point of formation mechanisms and animal raising techniques (Cang et al, 2004; Huang et al, 2015; Wang et al, 2015). The aforementioned research tends to concentrate in some parts of China, specifically the north and northeastern areas (Wang et al, 2018; Yang et al, 2012; Zhang et al, 2014).…”
Section: Background Of the Researchmentioning
confidence: 99%
“…According to Stuart et al (2012) and Ma et al (2011), the majority of organic and inorganic pollutants, including nitrogen (N), phosphate (P), fertilisers, organic pesticides, and other contaminants, are the main causes of nonpoint source pollution. Agricultural practices accounted for the vast majority of nitrate contamination and nonpoint source pollution (Wang et al 2015). The far-reaching, uncertain, and long-lasting effects of agricultural nonpoint source pollution make its regulation significantly more challenging than those of industrial pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The far-reaching, uncertain, and long-lasting effects of agricultural nonpoint source pollution make its regulation significantly more challenging than those of industrial pollution. Consequently, it is of utmost importance to address nonpoint source pollution by doing relevant research (Wang et al, 2015;Taebi and Droste, 2004;Guo et al, 2014). Surface and groundwater nitrate pollution is the most pervasive contaminant.…”
Section: Introductionmentioning
confidence: 99%